Curcuminoid compounds isolated from curcuma domestica val. as corrosion inhibitor towards carbon steel in 1% NaCl solution - Dias Kandias,; Bunbun Bundjali,; Deana Wahyuningrum, (Universiti Kebangsaan Malaysia, 2011)
The corrosion inhibitor of carbon steel in 1% NaCl solution by curcuminoids has been studied at 27oC using weight loss and electrochemical method. The determination of corrosion inhibition efficiency (%eff) utilising weight loss method at the concentration of 80 ppm showed the best result of 78.70% for third isolated fraction. Further determination utilising Tafel method showed the following results: raw pure extract of curcuminoid gave 89.88% at 50 ppm; the first isolated fraction gave 46.50% at 80 ppm; the second isolated fraction gave 44.83% at 30 ppm; and the third isolated fraction gave 92.44% at 70 ppm. Based on the analysis of Tafel extrapolation curve, the raw pure extract and the third fraction of curcuminoid acted as anodic inhibitor, whereas the first and the second fraction performed as cathodic inhibitors. The evaluations of synergism parameter (Sθ) indicate that the enhancement in inhibition efficiency towards raw pure extract was caused by the presence of second and third fractions as cathodic and anodic inhibitors. The contribution of steric hindrance of methoxy groups in curcuminoid structure causes the decrease in curcuminoid activity to be adsorbed on the electrode (carbon steel) surface.